Data on metabolic profile of insulin-degrading enzyme knockout mice - Borges, Diego O. (2019)
Insulin-degrading enzyme (IDE) degrades and inactivates bioactive peptides such as insulin. As insulin is a master regulator of glucose homeostasis, lack of IDE is expected to have a profound impact on both insulin and glucose levels. This article shares data on glucose and insulin homeostasis of control, heterozygous and knockout mice for Ide after 18 weeks of a normal chow diet. This data article is related to a research article entitled “Knockout of insulin-degrading enzyme leads to mice testicular morphological changes and impaired sperm quality” (Meneses et al., 2019).